2019
DOI: 10.4149/bll_2019_157
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of extended-spectrum β-lactamase (ESBL) and/or carbapenemase producing Enterobacteriaceae (CPE) and their antimicrobial resistance

Abstract: OBJECTIVES: We focused on detecting the most frequent resistance mechanisms in selected multidrugresistant (MDR) strains and determining their antimicrobial resistance. BACKGROUND: MDR pathogens pose urgent public health threat due to limited treatment options, rigorous control measures and signifi cant mortality. METHODS: We confi rmed extended-spectrum β-lactamase (ESBL) and carbapenemase producing Enterobacteriaceae through guidelines, as well following β-lactamases: AmpC by cloxacillin, class A carbapenema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…For example, the mechanism with the highest prevalence (38.1%) is once again the β-lactamase enzymes, which also provide special resistance to beta-lactam antibiotics (penicillins, cephalosporins, monobactams, and carbapenems). 21,22 Likewise, with a prevalence of (9.5%), mechanisms very similar to those described above were found. 23 Among them are: Alteration of porins (Omp35 and Omp36), efflux pumps, LPS modification system, PMQR determinants, and finally with a lower prevalence (4.8%) were found: DNA gyrase mutations, mutation of antibiotic targets, QRDR determinants, gyrB mutation and mutation in the AmpR repressor .24,25 It is important to clarify that due to the similarity of intrinsic resistance mechanisms between Klebsiella pneumoniae and Enterobacter spp.…”
Section: Intrinsic Mechanisms Of Multidrug Resistance To Antibiotics ...supporting
confidence: 77%
See 1 more Smart Citation
“…For example, the mechanism with the highest prevalence (38.1%) is once again the β-lactamase enzymes, which also provide special resistance to beta-lactam antibiotics (penicillins, cephalosporins, monobactams, and carbapenems). 21,22 Likewise, with a prevalence of (9.5%), mechanisms very similar to those described above were found. 23 Among them are: Alteration of porins (Omp35 and Omp36), efflux pumps, LPS modification system, PMQR determinants, and finally with a lower prevalence (4.8%) were found: DNA gyrase mutations, mutation of antibiotic targets, QRDR determinants, gyrB mutation and mutation in the AmpR repressor .24,25 It is important to clarify that due to the similarity of intrinsic resistance mechanisms between Klebsiella pneumoniae and Enterobacter spp.…”
Section: Intrinsic Mechanisms Of Multidrug Resistance To Antibiotics ...supporting
confidence: 77%
“…Similar figures were reported by Bartoloni et al 14,19,20 The sensitivity of the strains to amikacin in the present work coincides with authors from Bolivia and Venezuela, who published sensitivity figures above 90 %. 14,21 In Cuba, in a national study, resistance values were observed for trimethoprim-sulfamethoxazole (49 %), gentamicin (43 %), and nalidixic acid (38 %). 22. Another relevant finding was the high percentages of resistance to the three thirdgeneration cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the colistin-MIC distribution was less favourable for NDM-strains, with values far from the breakpoint, which may be a disadvantage when a combination treatment is considered. Growing numbers of colistin-resistant CRKP isolates were also reported from University Hospital facilities in the Slovak Republic, even if not so alarming—from 0% published in 2019 to 2.5% in 2022 [ 3 , 4 ]. When analysing this extremely high colistin-resistance rate in the CMH among the NDM CRKP strains, the most probable reason is the epidemic spread of the same colistin-resistant NDM Klebsiella pneumoniae strain during the COVID-19 period (as discussed above).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence and spread of carbapenem-resistant Klebsiella pneumoniae (CRKP) in hospitals worldwide [ 1 , 2 ], including the Slovak Republic [ 3 , 4 ], represent an urgent global public health issue, posing an enormous burden on hospital settings caring for high-risk patients [ 5 ]. Infections caused by these bacterial agents represent a significant therapeutic problem, primarily in patients in intensive care units, where bacterial superinfections increase the morbidity and mortality rates of critically ill and debilitated patients, with an overwhelming impact on hospitalisation costs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, in the era of increasing antimicrobial resistance among microorganisms, extensive research on new and more effective antibiotics is facilitated (9). On the other hand, alternative non-antibiotic treatments are applied, and the old and forgotten antimicrobial therapeutic options are being rediscovered.…”
Section: Introductionmentioning
confidence: 99%